Myeloid-Derived Suppressor Cell Differentiation in Cancer: Transcriptional Regulators and Enhanceosome-Mediated Mechanisms - Fultang, Norman; Li, Xinyuan; Li, Ting; Chen, Youhai H. (Frontiers in Immunology, 2021)
Myeloid-derived Suppressor Cells (MDSCs) are a sub-population of leukocytes that are important for carcinogenesis and cancer immunotherapy. During carcinogenesis or severe infections, inflammatory mediators induce MDSCs via aberrant differentiation of myeloid precursors. Although several transcription factors, including C/EBPβ, STAT3, c-Rel, STAT5, and IRF8, have been reported to regulate MDSC differentiation, none of them are specifically expressed in MDSCs. How these lineage-non-specific transcription factors specify MDSC differentiation in a lineage-specific manner is unclear. The recent discovery of the c-Rel–C/EBPβ enhanceosome in MDSCs may help explain these context-dependent roles. In this review, we examine several transcriptional regulators of MDSC differentiation, and discuss the concept of non-modular regulation of MDSC signature gene expression by transcription factors such as c-Rel and C/EBPß.